Postoperative Nausea and Vomiting After Craniotomy: An Evidence-based Review of General Considerations, Risk Factors, and Management. Issue 3 (4th July 2021) - Uribe, Alberto A.; Stoicea, Nicoleta; Echeverria-Villalobos, Marco; Todeschini, Alexandre B.; Esparza Gutierrez, Alan; Folea, Antonia R.; Bergese, Sergio D.
Abstract : One of the most common and distressing symptoms after craniotomy is postoperative nausea and vomiting (PONV). PONV could generate delayed postanesthesia care and hospitalization discharge, lower patient satisfaction, and an increase in overall hospitalization costs. The incidence of reported PONV after craniotomy is 22% to 70% without prophylaxis, and a multimodal regimen of medication has been recommended. We conducted a comprehensive literature review of the clinical evidence related to PONV prevention and management after craniotomy. All clinical trials in adult populations relevant to PONV after craniotomy available in English language and indexed in PubMed, Google Scholar and Cochrane Library databases from January 1997 up to September 2018 were retrieved using a combination of free-text words related to PONV in craniotomy. After screening manuscripts identified in the initial search, 23 clinical trials investigating systemic pharmacological intervention versus placebo or active control in patients undergoing craniotomy under general anesthesia met the criteria for inclusion in this comprehensive narrative review. The pathophysiology and mechanisms of PONV after craniotomy could be multifactorial in etiology. Therefore, based on current evidence, PONV management after craniotomy should focus on perioperative patient assessment, surgical, and anesthesia-related risk factors and the selection of systemic pharmacological considerations to reduce its incidence and complications. A multimodal regimen of medication targeting different chemoreceptors in the vomiting center is recommended. Ondansetron and dexamethasone, or their combination, are the most frequently used and effective agents. Further randomized clinical trials comparing different regimens that significantly reduce the incidence of PONV in craniotomy would provide relevant evidence-based data for PONV management in this patient population.